Investigation of indoor air quality for enclosed space application using electric-powered mini excavator - Rawi, Mohd Asyraf (2016)
This study investigates the indoor air quality for enclosed space application using electric powered mini excavator. The main content of this study is the indoor air quality for enclosed space application that is cause by mini excavator which is powered by gasoline engine and by electric motor. The impacts of indoor air quality in this enclose space room are ultimately determined by levels of contaminants and comfort parameters (i.e. temperature, carbon dioxide and carbon monoxide). There are a number of relationships that could be useful in discussing temperature, carbon dioxide and carbon monoxide and indoor air quality, such as the impact of carbon dioxide to a worker (i.e. low comfort level, body odor) and the impact of carbon monoxide to a worker (i.e. slight headache, cardiovascular effect, etc.). In this study, carbon dioxide and carbon monoxide have been used as an indicator of indoor air quality due to both to its use as tracer gas for air change rate estimation. The study has been conducted on same enclosed space room with different type of mini excavator. If air quality and comfort are appropriate for running mini excavator powered by electric motor (according to WHO guidelines) and~ on the other, to establish whether mini excavator powered by gasoline engine is exceed a recommended exposure limit (according to WHO guidelines), acquired data is useful in defining indoor air quality.